Pengaruh Debt To Equity Ratio Terhadap Profitabilitas Lembaga Keuangan (Studi Pada Bank BTPN Syariah Periode 2018-2023) - Toni Adhitya (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2025)
The purpose of this study is to determine the condition of the Debt To Equity Ratio, the condition of Return On Equity and the effect of Debt To Equity Ratio on Return On Equity at Bank BTPN Syariah for the period 2018-2023. This study uses a quantitative approach and secondary data based on time series data. Data were obtained from monthly financial reports published by Bank BTPN Syariah for 2018-2023 with a population of 72. The results of this study indicate that the condition of the Debt to Equity Ratio of Bank BTPN Syariah based on statistical analysis is in a less condition. Meanwhile, the condition of the Return On Equity of Bank BTPN Syariah based on statistical analysis is in the less category. The results of the correlation analysis between Debt to Equity Ratio and Return On Equity are -0,035, which means that it has a moderate and opposite or negative relationship. The t-value is -0,294 with a significance value of 0.000, which means that Ha is accepted and H0 is rejected. The results of the Debt to Equity Ratio determination coefficient have an effect of 15,5% on Return On Equity. While the remaining 84,5% is influenced by other variables outside this study.